Impact of action observation therapy on motor and cognitive outcomes in older adults with mild cognitive impairment: a randomized controlled study - Martin-Blazquez, Miriam; Sosa-Reina, M. Dolores; Andrade-Granda, Angye Micaela; Sanz-Esteban, Ismael; López-Ruiz, Javier; Estrada Barranco, Cecilia (Frontiers in Public Health, 2025)
BackgroundMild Cognitive Impairment (MCI) affects both cognitive and motor function, increasing the risk of immobility, falls, and compromising independence. The aim of this study is to determine whether implementing Action Observation Therapy (AOT) in a population with MCI would yield positive outcomes in cognitive status, in activities of daily living (ADLs), upper limb (UL) functionality, gait and balance, and if these results differ based on the observation modality employed.MethodsThirty participants, aged 65 and above with MCI, were assigned to three groups: therapist observation group (TOG), peer observation group (POG), and control group (CG). The intervention comprised physical and cognitive exercises over 5 weeks, with assessments before and after.Resultssignificant differences in post-intervention improvement were found between the groups, excluding the Box and block test. No significant differences were found between the TOG and POG in any improvement variable. Significant differences were found between the CG and the observation groups.ConclusionsThe intervention with AOT proved beneficial for individuals with MCI, yielding significant results both when observing the therapist and when observing a peer compared to the CG, in the domains: cognition, ADLs, gait and balance.